Avaliação dos efeitos do exercício físico na lesão estriatal unilateral por 6-ohda em ratos - Costa, Roberta Oliveira da (2016)
Parkinson's disease (PD) is a neurodegenerative disorder caused by the loss of dopaminergic cells in the nigrostriatal tract, with a corresponding reduction in the contents of dopamine (DA) in the striatum. In this scenario, the present study aimed to evaluate the beneficial effects of exercise on unilateral striatal lesion with 6-OHDA. For this, we used male Wistar rats (200-250 g) divided into 4 groups: FO (without exercise), FO (with exercise), 6-OHDA (without exercise), 6-OHDA (with exercise), who received injections 6-OHDA (12 ug / 2μl) or saline (FO) in the right striatum by stereotactic surgery. The exercise was performed for 14 days, for 30 minutes at a speed of 20 cm / second beginning 24 hours after the surgical procedure. Then the animals were submitted to behavioral tests and, after that, they were euthanized and the areas of the brain (prefrontal cortex, hippocampus and striatum) were used for immunohistochemistry and neurochemical measurements. Data were analyzed by ANOVA and Tukey test (post hoc test) and considered significant at p <0.05. The results showed that physical exercise promotes a significant decrease in the number of contralateral rotations induced by apomorphine as well as an improved engine performance, increased horizontal exploratory activity and rearing and decreased grooming number in the open field test. We also observed a reversal of memory deficits when challenged in the Y-maze and object recognition. The levels of dopamine (DA) and metabolites decreased in the striatum of the injured group and this effect was partially reversed by exercise. The results of oxidative stress showed that exercise promoted a reduction in the MDA content and production of nitrite/nitrate. Exercise increased BDNF level when related to the non-exercise group. The immunoreactivity for tyrosine hydroxylase (TH) had a significant reduction on the right (lesioned) side of striatum in the 6-OHDA group when compared to the lesioned and subjected to exercise group. Taken together, the results of this study indicate the potential of physical exercise as a DP modifier, being able to relieve the motor and cognitive deficits in animals submitted to the experimental model of PD by reducing DA depletion in the striatum, significantly increasing BDNF levels, reducing oxidative stress, providing neuroprotection and, thus, contributing to the prevention and treatment as a pharmacological tool that can alleviate the symptoms of PD.